P252 Low adherence is associated with worse disease course in Ulcerative Colitis: a retrospective study from a single referral center. (21st January 2022) - Viola, A; Demarzo, M G; Abbruzzese, A; Chiappetta, M F; Costantino, G; Alibrandi, A; Fries, W
Abstract: Background: New therapeutic approaches for ulcerative colitis (UC) are becoming available but still there is no robust evidence for predictors of poor outcome. We aimed to evaluate factors associated with a more aggressive UC course. Methods: Data of all UC outpatients followed for at least 3 years after diagnosis were retrospectively collected. Demographic, anamnestic data, disease characteristics and treatment were collected. Disease patterns were defined according to the IBSEN study (Henriksen M. et al 1 ). Disease worsening at 3 years was defined as the presence of disease extension at endoscopy, proctocolectomy and or early use of biologics. Risk factors for chronically active disease were assessed. Moreover, the following outcomes were explored according to disease extent at diagnosis (E1-E2 vs E3): corticosteroid free remission, hospitalization, early use of immunomodulators and biologics, colorectal cancer, adherence, mucosal healing at 3 years. Survival analysis was carried out to estimate the probability of receive a biological treatment within 3 and 5 years from diagnosis according to disease extent (E1 vs E2 vs E3) and disease patterns. Results: A total of 345 UC patients were included and followed for a mean period of 94 months. Patients with extensive colitis had a higher rate of colectomy (p < 0.001), hospitalizations (p=0.004) and of chronically active disease 3 years after diagnosis (p < 0.001) and were more likely to receive early biologics and IMM (p= 0.04 and p=0.01 respectively) (Figure 1 ). The only factor associated with chronic active disease was non-adherence (p < 0.03; OR 0.49, 95% CI: 0.26–0.95) (Table 1 ). No differences were found for the probability to receive biologics within 3 and 5 years from diagnosis according to Montreal extension at diagnosis and disease pattern. Conclusion: Patients diagnosed with pancolitis were more likely to underwent colectomy or to have a chronically active disease with a higher rate of hospitalization, early use of IMM or biologics. The only predictor for chronically active UC was the lack of adherence to therapy within the first 3 years after diagnosis. Reference: 1. Henriksen M, et al; IBSEN Study Group. Ulcerative colitis and clinical course: results of a 5-year population-based follow-up study (the IBSEN study). Inflamm Bowel Dis. 2006;12:543–50. The study was supported by a grant from Ferring S.p.A.